Analysis of the Impact of YouTube Social Media on the Morals of Elementary School Students - Febriyanti Febriyanti; Ana Andriani; Isti Windi Astuti (Proceedings Series on Social Sciences & Humanities, 2025)
This research aims to analyze the impact of YouTube social media on the morals of elementary school students, considering the increasing popularity of this platform among children. The method used is a qualitative approach with a phenomenological method. The sources of information include students, parents, and teachers to collect data on the types of YouTube content accessed and its influence on students' attitudes. Data collection techniques employed are observation, interviews, and documentation. Data analysis techniques involve data reduction, data presentation, and conclusion drawing. The results of this study indicate that YouTube social media can have a positive impact through educational content; however, it can also lead to negative effects due to exposure to inappropriate content that has the potential to cause deviant behavior, thereby affecting students' morals. This research also emphasizes the importance of the roles of parents and teachers in supervising YouTube usage and the need for a proactive approach in educating children about the wise and responsible use of social media.